Biochemical analysis of biomass and cysts of brine shrimp Artemia sp. from some salt lakes of the Pavlodar area populations (Experimental biology, 2018)
In recent years increased the demand for valuable resources of hyperhaline water bodies of Kazakhstan - cysts and the brine shrimp Artemia sp. as an indispensable starter feed for most species of fish, marine crustaceans, farm animals. Brine shrimp biomass has high protein content with a significant level of essential amino acids, hormones, carotenoids, vitamins, valuable fatty acids. Artemia is characterized by extremely rapid growth, accelerated puberty and high fertility, which is important for maintaining the population. For these reasons, Artemia is a valuable source of protein in feed production. Value of brine shrimp used as feed depends on its biochemical composition, which is influenced by such environmental factors as temperature, salt concentration, oxygen content etc. In this regard, different populations from different natural sources vary in composition and have different feeding value.The article considers the biochemical composition of the biomass and cysts of brine shrimp selected from 12 salt lakes of Pavlodar region of Kazakhstan. It is established that the investigated objects were characterized by high protein content (average of 42.38 g%), free amino acids (average 114,34 mg%), lipids (average of 37.69 g%), while the content of total fats in the cysts was lower than in the crustaceans 4.7 times; the average value of the mass fraction of glucose in Artemia populations did not exceed 2.5 g%; the cysts contained more than 1 g% total carbohydrates; glycogen content in cysts and biomass were approximately equal. There were seasonal fluctuations in the content of dry matter, free amino acids, common lipids, common carbohydrates and glycogen in the biomass of the studied populations.